ANALISIS INDEKS PEMBANGUNAN MANUSIA DI PROVINSI PAPUA - Joko Hadi Susilo; M Kholilurrohman; Zainul Hasan (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2020)
This study aims to determine the factors that influence the human development index in Papua Province in 2006-2015. This research method uses descriptive quantitative analysis with eviews v.10. The population of this study is in 29 Regencies / Cities in Papua Province so that the sample in this study amounted to 290 samples obtained through secondary statistics from the Central Bureau of Statistics (BPS).The results showed that together the number of unemployment, poverty rate, gini ratio and total population effect on the human development index. The poverty rate negatively has a negative effect on the human development index. The number of unemployment and the gini ratio have a positive effect on the human development index. The total population does not effect on the human development index. The results of the study suggested that the government conduct several policies such as eliminating the gini ratio, controlling the population, reducing unemployment and poverty rate.